LEGAL POSITION OF PAYLATER AS A PAYMENT METHOD IN INDONESIA - David Banjarnahor; Alifah Nur Fitriana Naridha Naridha; Tengku Andrias Prayudha; Sy. Muhamamad Ikhsan; Auliya Rochman (Authentica: Private Law Journal, 2025)
This study examines the perspective of the juridical status of the implementation of the payment system and its legality dimension in social practice using the statute approach and conceptual approach methodology. To examine the problem of this research method, it uses normative juridical by using a conceptual approach to review and study the research topics raised. The findings indicate that the increasing adoption of payout immediately raises new complexities in users' understanding of rights and obligations in digital contracts. Regulatory uncertainty makes consumers vulnerable to debt traps due to the consequences of late payments, and the risk of personal data leakage increases as the use of pay later services is not equipped with adequate data protection. It is time for Bank Indonesia and the Financial Services Authority to be clearer in identifying concrete steps to improve financial literacy and consumer supervision in line with the development of increasingly developing and innovative pay laters. Based on a comprehensive analysis, it can be concluded that the legal position of the payout mechanism is equivalent to traditional credit agreements in general.